Studi Perhitungan Laju Reaksi Neutron Dalam Reaktor SCWR (Supercritical Water Reactor) Model Perangkat (Assembly) Heksagonal Berbahan Bakar Thorium - Apriliana Apriliana; Yanti Yulianti; Pulung Karo Karo (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2018)
The calculation of fission and capture reaction rate with and without filter has been done using REACT of SRAC. In material 1 fission reaction rate with and without filter were increased by increasing percent of U233. The highest fission reaction rate with filter was 5,7194x10-2reaction/cm3sand without filter was 6,1361x10-2 reaction/cm3s. Meanwhile capture reaction rate with and without filter were decreased by increasing percent of U233. The highest capture reaction rate with filter was 2,2156x10-2 reaction/cm3s and without filter was 2,4906x10-2 reaction/cm3s. In material 3, fission and capture reaction rate with and without filter were decreased by increasing percent of U233 in material 1. The highest fission reaction rate with filter was 1,5218x10-2 reaction/cm3s and without filter was 1,6293x10-2reaction/cm3s. The highest capture reaction rate with filter was 2,2156x10-2 reaction/cm3s and without filter was 2,3993x10-2reaction /cm3s. Neutron reaction rate with filter was smaller than neutron reaction rate without filter